KERENTANAN PULAU SOPHIALOUSIA DI KABUPATEN LOMBOK BARAT TERHADAP PERUBAHAN IKLIM DAN KONSEP PENANGANANNYA - Kadek Windy Candrayana; I Gusti Agung Putu Eryani (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2023)
Climate change due to increasing temperatures causes changes in sea conditions. Rising sea levels and increasing the occurrence of high waves are the impacts of climate change. This condition threatens the existence of small islands, including Indonesia. One of the islands that is vulnerable to this condition is Sophialousia Island which is the southern border of Indonesia and Australia. The vulnerability of Sophialousia Island was analyzed using the Integrated Coastal Vulneron ability Index (ICVI) and adding sea level rise parameters. The number of parameters reviewed are 7 (seven) parameters, namely the type of coastal slope, beach conditions, the percentage of coastal protection, storm events, rob events, sea level rise (SLR), and land use. CMS-Wave modelling is used for strategy simulation handling to reduce the risk of island vulnerability. The results of the vulnerability assessment by ICVI showed that Sophialousia Island was classified as high vulnerability due to climate change. So the recommended handling strategy is to build a floating breakwater and make a revetment. The floating breakwater reduces storm surges, and the revetment increases the island's elevation so it is resistant to SLR.